Modified intramedullary nail to treat diaphyseal femoral fracture in a dog - Case report - De Freitas, Silvio Henrique [UNESP]; Dória, Renata Gebara Sampaio; Minto, Bruno Watanabe [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Melo, Marcos Marini; De Camargo, Lázaro Manoel; Santos, Marcelo Diniz Dos; Shimano, Antonio Carlos; Ambrósio, Carlos Eduardo (My University, 2013)
The long bone fractures play a major role in clinical-surgical routine, both in veterinary and human medicine. Due to the frequency in which they occur it is clear the necessity for reparative orthopedic procedures. Among the treatment techniques, the method of interlocking nail provides rigid stabilization of diaphyseal fractures and has biomechanical advantages compared to other stabilization techniques. We report a case of femoral fracture in a dog treated with the use of a modified intramedullary interloking nail, made of Steinmann pin and polymethylmethacrylate. We were able to realign the proximal and distal bone fragments, achieving the fracture healing and the patient return to normal activities. It is concluded that the use of intramedullary modified technique is efficient and can be used as an additional option in the treatment of diaphyseal femoral fractures in dogs.
Haste intramedular modificada no tratamento de fratura diafisária de fêmur em cão - Relato de Caso
Keywords: Canine; Femur; Modified interloking nail; Polymethylmethacrylate